2019
DOI: 10.1161/strokeaha.118.024347
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Accuracy of the Spot Sign for Predicting Hematoma Growth and Clinical Outcomes

Abstract: Background and Purpose— The computed tomography angiographic spot sign refers to contrast leakage within intracerebral hemorrhage (ICH). It has been proposed as a surrogate radiological marker for ICH growth. We conducted a meta-analysis to study the accuracy of the spot sign for predicting ICH growth and mortality. Methods— PubMed, Medline, conference proceedings, and article references in English up to June 2017 were searched for studies reporting “co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Reported sensitivity of the SS for predicting HE ranges from 21% to 93%, with two recent meta-analyses showing a pooled sensitivity of 62% and 57% respectively. 2,4,7,[17][18][19][20][21][22][23][24][25] We found a low sensitivity of 32% of the SS on conventional-like mixed arterial phase imaging for predicting HE. While we set no limitation in the onset or LSW-toscan time in order to not exclude late expanders, many former studies only included patients with an onset-to-scan time ≤6 hours.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Reported sensitivity of the SS for predicting HE ranges from 21% to 93%, with two recent meta-analyses showing a pooled sensitivity of 62% and 57% respectively. 2,4,7,[17][18][19][20][21][22][23][24][25] We found a low sensitivity of 32% of the SS on conventional-like mixed arterial phase imaging for predicting HE. While we set no limitation in the onset or LSW-toscan time in order to not exclude late expanders, many former studies only included patients with an onset-to-scan time ≤6 hours.…”
Section: Discussionmentioning
confidence: 61%
“…Two meta-analysis showed a rather low pooled sensitivity of 57% and 62% of the SS for predicting HE. 2,7 Assessment of SS on CTA might be challenging as it is difficult to differentiate hyperdense hemorrhage from contrast agent. Dual-energy CTA (DE-CTA) is a technique that uses high-and low-peak voltage acquisitions simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that the spot sign is an independent risk factor for HE and poor clinical outcomes ( 27 30 ), with a sensitivity of 62% and a specificity of 88% ( 30 ). Previous studies also reported that the incidence of spot sign ranged from 19 to 46%, despite different time intervals between the onset of symptoms and initial imaging ( 15 , 29 , 31 ). In the present study, we detected the spot sign in 31.5% of our patient cohort; this incidence was similar to that reported previously.…”
Section: Discussionmentioning
confidence: 91%
“…Spontaneous intracerebral hemorrhage (ICH) is associated with high mortality and poor outcome ( 1 ). Studies found various indicators for predicting outcome following ICH ( 2 4 ); however, few of these involve biochemical tests. The brain injury after ICH includes the primary injury, which is the mechanical damage of the adjacent tissues by hematoma within the first hours after ICH, and the secondary injury, which is initiated by the extravasation of blood products into the brain parenchyma ( 5 ).…”
Section: Introductionmentioning
confidence: 99%